Stroke case fatality in sub-Saharan Africa: Systematic review and meta-analysis - Adoukonou, Thierry; HOUINATO, Dismand (My University, 2021)
Abstract Background The burden of stroke is high in sub-Saharan Africa; however, few data are available on long-term mortality. Objective To estimate over one-month stroke case fatality in sub-Saharan Africa. Methods A systematic review and meta-analysis were performed according to meta-analysis of observational studies in epidemiology and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PROSPERO protocol: CRD42020192439), on five electronic databases (PubMed, Science direct, AJOL, EMBASE, and Web of Sciences). We searched all studies on stroke case fatality over one month in sub-Saharan Africa published between 1st January 2000 and 31st December 2019. Results We included 91 studies with a total of 34,362 stroke cases. The one-month pooled stroke case-fatality rate was 24.1% [95% CI: 21.5–27.0] and 33.2% [95% CI: 23.6–44.5] at one year. At three and five years, the case-fatality rates were respectively 40.1% [95% CI: 20.8–63.0] and 39.4% [95% CI: 14.3–71.5] with high heterogeneity. Hemorrhagic stroke was associated with a higher risk of mortality at one month, but ischemic stroke increased the risk of mortality over six months. Diabetes was associated with poor prognosis at 6 and 12 months with odds ratios of 1.64 [95% CI: 1.22–2.20] and 1.85 [1.25–2.75], respectively. Conclusion The stroke case fatality over one month was very high, compared to case fatalities reported in Western countries and can be explained by a weak healthcare systems and vascular risk factors.
Keywords: Stroke; case fatality; sub-Saharan Africa; one month; systematic review